Performing journalism: Making sense of ethical practice within local interloper media - Hujanen Jaana; Ruotsalainen Juho; Vaarala Viljami; Lehtisaari Katja; Grönlund Mikko (Sage, 2022)
This paper explores the blurring boundaries between local journalism, strategic and marketing communications and civic information. The study at hand produces new knowledge regarding the conceptions and practices that are emerging in the middle ground between local journalism and communications. The data consist of 10 thematic in-depth interviews with writers, owners and other key personnel from Finnish local communications operations applying journalistic practices in their content production, conceptualised here as interloper media practitioners. By applying the concept of boundary work, the study sheds light on the discursive contest over the forms and vocabulary of journalism and news media. The study also explores the ethical guidelines interloper media apply and how their representatives reflect on their ethical code of practice. The results are condensed into five rationales the practitioners use to justify the legitimacy of the interloper media outlets and the use of journalistic methods in strategic or commercial communications and civic information. The practitioners experience the boundaries between journalism and various types of communications as blurring. They borrow and apply journalistic styles and ethical guidelines selectively to lend their media attractivity and credibility. They face ethical conflicts in their work particularly regarding their relationship to power holders and decision-makers. Yet a culture of profound ethical reflection is markedly absent from their accounts.